DEVELOPMENT OF A TARGETED PROTEOMICS ASSAY FOR QUANTIFICATION OF ANGIOTENSIN PEPTIDES IN THE RENIN ANGIOTENSIN ALDOSTERONE SYSTEM. (June 2022) - Bernieh, Dennis; Lane, Dan; Rufus, Prabha; Osman, Hanad; Salim, Farah; Alghamdi, Randah; Jenkins, Sian; Gill, Henry; Ng, Leong; Jones, Don; Gupta, Pankaj
Abstract : Objective: The canonical renin–angiotensin aldosterone system (RAAS) has been extensively studied and methods are available for use clinically to assess hypertension. The non-canonical axis of the RAAS (consists of angiotensin 1–7, angiotensin 1–9, angiotensin-converting enzyme 2 and alamandine) counteract the effects of the canonical pathway. This reveals their role as potential therapeutic targets for cardiovascular disease but it has not been studied in detail in the clinical or research setting due to the difficulty in measuring its components. Furthermore, the functional balance between the two arms of RAAS has not been fully understood. Design and method: A multi-marker liquid chromatography coupled with triple quadrupole mass spectrometry (LC-MS/MS assay) was developed and optimised to simultaneously quantify 10 peptides (angiotensin II, Ang III, Ang IV, ACE2, Ang 1–5, Ang 1–7, Ang 1–9, Ang 1–12, Alamandine and Ang A) in the RAAS pathway. For the preparation of calibration samples, 50 L of bovine serum albumin (BSA) was spiked with the 10 peptides standards and extracted by solid phase extraction using their respective internal standards. Chromatographic analyses were performed on an Acquity C18 Premier peptide column using gradient elution with a run time of 8 min. Identification was carried out using electrospray ionisation (positive) on a Waters Xevo TQ-XS triple quadrupole mass spectrometer. The developed assay is currently undergoing validation in line with international guidelines. Results: The method shows good linearity. The accuracy (relative error) and precision (coefficient of variation) values were within the pre-defined limits of within 15% at all tested concentrations for the target peptides. The assay sensitivity was sufficient to detect the peptides in plasma samples. Conclusions: The multimarker LC-MS/MS assay development was successful and following completion of validation has the potential to quantify the levels of these vasoactive peptides in patients with hypertension. This has been achieved, for the first time to the best of our knowledge on the entire RAAS pathway. This multimarker LC-MS/MS based proteomics assay could be used to study patients with hypertension in both research and clinical settings.